How to obtain $y'$ from $e^{y}=x^{\ln x}$?

This is what I did: $$\ln e^y = \ln x^{\ln x}$$ $$y = \ln ^2 x$$ $$y' = \frac{2 \ln x}{x}$$ Is this correct? When I compare it with an online derivative calculator, the result they gave was different, and they used implicit differentiation instead.

  • 2
    $\begingroup$ Seems fine to me. Graphs look good too. $\endgroup$ – mvw Feb 16 '17 at 9:11
  • 5
    $\begingroup$ I'd avoid $\ln^2x$, which is ambiguous, preferring $(\ln x)^2$; this said, you did perfectly right. $\endgroup$ – egreg Feb 16 '17 at 9:43

So if we use implicit differentiation:


But $e^{y} = x^{\ln(x)}$, so:

$$\frac{\mathrm{d}y}{\mathrm{d}x}=2\ln(x) \frac{x^{\ln(x)-1}}{x^{\ln(x)}}=\frac{2\ln(x)}{x}$$

So you are quite right in your answer (and your approach is absolutely fine too!)


$$(e^y)'=e^yy'$$ and $$(e^{ln^2x})'=(\ln^2x)'e^{ln^2x}=2\frac{\ln x}xe^{ln^2x}.$$

Then dividing by $e^y=e^{ln^2x}$,

$$y'=2\frac{\ln x}x.$$

As expected, same answer, though a little more tedious.

This is $$g(y)=f(x),\\ g'(y)y'=f'(x),\\ y'=\frac{f'(x)}{g'(y)}=\frac{f'(x)}{g'(g^{-1}(f(x)))}$$ versus $$y=g^{-1}(f(x)),\\ y'=\frac{f'(x)}{g'(g^{-1}(f(x)))} $$ by the formula for the inverse function and the chain rule.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.